STRATEGI DUAL-CURRICULUM DALAM IMPLEMENTASI PENDIDIKAN MULTIDISIPLIN DI PONDOK PESANTREN MODERN - Ali Masdar Fahim; Agus Nuril Anwar; Ahmad Sirojul Mabrur; Muhammad Umar Faruq; Muhammad Adib (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Religious education (Salaf) and modern science are two contrasting elements that generate graduates who are either religiously competent yet retrograde in terms of technology, or the reverse. Conversely, this research aims to explore and examine the application of the multidisciplinary approach at Pondok Pesantren Modern Al-Rifa’ie 3 Malang, specifically how the creating body manages its continuity within traditional frameworks, known as